Exploring Veterinary Students’ Practice and Challenges in Using Quizizz for Critical Reading in a Private University - Wibowo, Amiruddin Hadi; Ulfaika, Romlah; Faridy, Azka (Universitas Muhammadiyah Gresik, 2025)
This study explores the effectiveness of Quizizz in enhancing critical reading skills among veterinary students in an ESP (English for Specific Purposes) course. Using a descriptive qualitative research design, the study involved 90 veterinary students from a private university who regularly use Quizizz for reading practice. Data were collected through surveys and semi-structured interviews, focusing on students' experiences, benefits, and challenges. The responses were analyzed using thematic analysis to identify key patterns related to learning effectiveness and obstacles. The results indicate that Quizizz enhances engagement, motivation, and reading comprehension by integrating gamified features such as instant feedback, leaderboards, and interactive questions. However, the study also found limitations in fostering deeper critical reading skills, as the platform primarily supports surface-level comprehension rather than higher-order thinking. Challenges such as technical issues, lack of personalized feedback, and stress from competition were also noted. To address these challenges, the study suggests integrating discussion-based activities, incorporating instructor feedback, balancing competition with collaboration, and designing questions that promote analytical thinking. Future research should explore how adaptive learning technologies and AI-driven tutoring can further support critical reading skills in veterinary ESP courses. Keywords: Quizizz, veterinary students, critical reading, gamification, digital learning,